Primary care providers' knowledge, attitudes, and practices related to prediabetes in China: A cross-sectional study - Pi, Linhua; Yan, Jianru; Fei, Dongxue; Zheng, Ying; Shi, Xiajie; Wang, Zhen; Zhou, Zhiguang (Frontiers in Public Health, 2023)
Background The management of prediabetes has great clinical significance, and primary care providers (PCPs) play important roles in the management and prevention of diabetes in China. Nevertheless, little is known about PCPs' knowledge, attitudes, and practices (KAP) regarding prediabetes. This cross-sectional study aimed to assess the KAP regarding prediabetes among PCPs in the Central China region. Methods This cross-sectional study was conducted using self-administered KAP questionnaires among PCPs from Central China region. Results In total, 720 PCPs completed the survey. Most physicians (85.8%) claimed to be aware of the adverse effects of prediabetes and reported positive attitudes toward prediabetes prevention, but the PCPs' knowledge of prediabetes and management practices showed substantial gaps. The prediabetes knowledge level and practice subscale scores of the PCPs were only 54.7% and 32.6%, respectively, of the corresponding optimal scores. Female PCPs showed higher prediabetes knowledge level scores (p = 0.04) and better practice scores (p = 0.038). Knowledge and attitude scores were inversely correlated with participants' age and duration of practice (p < 0.001). The PCPs who served in township hospitals had significantly higher knowledge and attitude scores than those who served in village clinics (p < 0.001). Furthermore, knowledge and practice scores increased with increasing professional titles. Recent continuing medical education (CME) attendance had a significant positive influence on knowledge of prediabetes (p = 0.029), but more than four-fifths of the surveyed PCPs did not participate in diabetes-related CME in the past year. Conclusions Substantial gaps were observed in PCPs' knowledge and practices regarding prediabetes in the Central China region. CME programmes were under-utilized by PCPs. Structured programmes are required to improve PCPs' prediabetes-related knowledge and practices in China.